Ecological Risk-Based Management of Aquaculture in Wadaslintang Reservoir - Wahyu Andi Susanto; Suradi Wijaya Saputra (Jurnal Biologi Tropis, 2026)
Wadaslintang Reservoir is a multipurpose reservoir used for power generation, irrigation, capture fisheries, and fish farming using a floating net cage (KJA) system. Intensification of this utilization has the potential to increase pressure on water quality and the sustainability of fish resources. This study aims to evaluate the condition of water quality, phytoplankton community structure, composition and size of fish catch, and their relationship to KJA cultivation activities in Wadaslintang Reservoir. The study was conducted through measuring physicochemical parameters of water at six observation stations, phytoplankton identification, analysis of fish catch composition, measurement of tilapia size, and collection of secondary data regarding KJA cultivation activities. The results showed that most water quality parameters, such as dissolved oxygen, temperature, nitrate, and ammonia, still met the quality standards for class III waters. However, the total phosphate concentration at several stations exceeded the quality standards, accompanied by relatively low clarity and the dominance of phytoplankton from the Chlorophyta and Cyanobacteria groups with a moderate diversity index (H' = 1.78), which indicates the presence of nutrient pressure leading to eutrophic conditions. The catch composition is dominated by tilapia (75.68%), with sizes that are generally still relatively small compared to mature gonad size. Production from marine cage cultivation is also dominated by tilapia (97.91%), potentially increasing nutrient loads if management is not adjusted to environmental carrying capacity. The results of the study indicate that Wadaslintang Reservoir is still suitable for fisheries, but requires capacity-based aquaculture management, increased feed efficiency, and regular water quality monitoring to maintain ecosystem sustainability.